Comparative pathology of the nasal epithelium in K18-hACE2 Tg mice, hACE2 Tg mice, and hamsters infected with SARS-CoV-2. Issue 4 (July 2022) - Yu, Pin; Deng, Wei; Bao, Linlin; Qu, Yajin; Xu, Yanfeng; Zhao, Wenjie; Han, Yunlin; Qin, Chuan
Severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) causes severe viral pneumonia and is associated with a high fatality rate. A substantial proportion of patients infected by SARS-CoV-2 suffer from mild hyposmia to complete loss of olfactory function, resulting in anosmia. However, the pathogenesis of the olfactory dysfunction and comparative pathology of upper respiratory infections with SARS-CoV-2 are unknown. We describe the histopathological, immunohistochemical, and in situ hybridization findings from rodent models of SARS-CoV-2 infection. The main histopathological findings in the olfactory epithelia of K8-hACE2 Tg mice, hACE2 Tg mice, and hamsters were varying degrees of inflammatory lesions, including disordered arrangement, necrosis, exfoliation, and macrophage infiltration of the olfactory epithelia, and inflammatory exudation. On the basis of these observations, the nasal epithelia of these rodent models appeared to develop moderate, mild, and severe rhinitis, respectively. Correspondingly, SARS-CoV-2 viral RNA and antigen were mainly identified in the olfactory epithelia and lamina propria. Moreover, viral RNA was abundant in the cerebrum of K18-hACE2 Tg mice, including the olfactory bulb. The K8-hACE2 Tg mouse, hACE2 Tg mouse, and hamster models could be used to investigate the pathology of SARS-CoV-2 infection in the upper respiratory tract and central nervous system. These models could help to provide a better understanding of the pathogenic process of this virus and to develop effective medications and prophylactic treatments.